PENDIDIKAN ANAK DALAM PERSEPSI MASYARAKAT - Fauzi Fahmi; Cindi Rantika (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2021)
The progress of a society, nation, and state is also determined by the progress of education carried out. This research is a qualitative research, with a descriptive type of research. The subjects in this study were people in Dusun II Gang Jati, Karang Anyar Village, Secanggang District by taking samples of 3 families whose children's education was low and 3 families whose children's education was good. Based on the results of this study, it was found that: 1) The people of Karang Anyar Village, Secanggang District realized the importance of children's education. Therefore, they provide children's education at home. 2) Parents also provide education to their children through formal education in schools, by providing education to their children they can develop children's knowledge under the guidance of teachers as educators in schools.